Specific features of taxation of in-dividuals in relationships with foreign elements. - K. Ponomareva (Правоприменение)
УДК 347.9Subject. The issues of taxation of residents and non-residents under Russian tax law are considered in the article. The problems of realization of non-discrimination principle under Russian tax law are brought into light. The important role of judicial practice in development of mechanisms of taxation of non-residents is brought into light.Aim. The aim of this paper is the design of the legal framework of taxation of residents and nonresidents under Russian tax law in the scope of implementation of OECD mechanisms in the legal regulation of income taxation.Methodology. The author uses methods of theoretical analysis, particularly the theory of integrative legal consciousness, as well as legal methods, including formal legal method and comparative law.Results, scope. The personal income tax under Russian tax law is a direct federal income tax. It occupies a special place in the tax system, affects the interests of almost all citizens, is fairly simple in administration, and the share of its receipt in the budget is high.The leading element of the legal construction of the tax considered in the article is the subject of taxation, and namely the peculiarities of the taxation regime, depending on whether the taxpayer has the status of a resident or non-resident. The main differences of the taxation of tax residents and non-residents in the Russian Federation are the following ones:the object of taxation for tax residents of the Russian Federation is income received from sources in the Russian Federation and (or) from sources outside the Russian Federation; for non-residents it is the income they received only from sources in the Russian Federation;the tax rate for tax residents of the Russian Federation is 13 percent; the tax rate for nonresidents is 30 percent.When determining the tax base, all incomes of the taxpayer, received by him in cash or in kind, or the right to dispose of which he has arisen, as well as income in the form of material benefits, are taken into account. Exceptions to this rule are provided for in Article 217 of the Tax Code, which contains a list of income exempt from taxation.Conclusions. The author comes to the conclusion that the legal regulation of the taxation of residents and non-residents is changing rapidly. Meanwhile, in the Russian legislation, the specifics of creating and terminating the status of a tax resident are not specified in detail. At the same time, several taxation regimes have been established for foreigners. This fact allows them to pay taxes at a general rate.